2020
DOI: 10.1111/1742-6723.13451
|View full text |Cite
|
Sign up to set email alerts
|

Trend of emergency department presentations with a mental health diagnosis in Australia by diagnostic group, 2004–05 to 2016–17

Abstract: Objective To examine trends of ED presentations with a mental health (MH) diagnosis in Australia and its jurisdictions by diagnostic group between 2004–05 and 2016–17. Methods Data comprised ED presentations with a principal diagnosis of ICD‐10‐AM F00–F99 (MHdx) captured within the National Non‐Admitted Patient Emergency Department Care Database. Trends in absolute number and rates of MHdx presentations per 10 000 population were assessed as differences (x‐fold) and annual growth rates (average and compound). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
5
31
0
Order By: Relevance
“…The individual collections are also the best available evidence, these administrative data used for other analyses . However, administrative data are also subject to a general lack of understanding of their potential usefulness, and thus the importance of robust coding practices . Further, as the jurisdictional collections and NNAPEDCD have historically only recorded one diagnostic code, there is an underestimation of MH presentations, as self‐harm and suicide‐related presentations are not coded as an F‐code but as X60‐X84, and may even be coded as injury (U50‐Y98) .…”
Section: Discussionmentioning
confidence: 99%
“…The individual collections are also the best available evidence, these administrative data used for other analyses . However, administrative data are also subject to a general lack of understanding of their potential usefulness, and thus the importance of robust coding practices . Further, as the jurisdictional collections and NNAPEDCD have historically only recorded one diagnostic code, there is an underestimation of MH presentations, as self‐harm and suicide‐related presentations are not coded as an F‐code but as X60‐X84, and may even be coded as injury (U50‐Y98) .…”
Section: Discussionmentioning
confidence: 99%
“…41 Summarised, the need to develop and expand the RNs’ understanding of the holistic aspects of their professional role is important and should be taken into account in when arranging EC. This is especially so when the care of people with mental illness in emergency departments may increase 6,7 and be adversely affected by diagnostic overshadowing and avoidance by clinical staff. 42…”
Section: Discussionmentioning
confidence: 99%
“…5 From an international perspective, an Australian study shows that the number of emergency department presentations increased between 2004 and 2016 across most mental illness diagnostic groups, but particularly psychoactive substance use-related disorders. 6 In addition, a US study showed that the number of children visiting emergency care with mental health illness had risen by 60% between 2007 and 2016. 7 Taken together, this provides a picture of mental illness increasing internationally for all ages and more specifically, an increase in emergency care (EC) visits due to such conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Intoxication is a primary barrier to quick assessment, and incidence of intoxication as a presenting or comorbid complaint is steadily rising. 1 Alcohol intoxication so heavily affects the reliability of assessment that disposition decisions often cannot be made, so patients may wait in ED until sober (possibly up to 12 h). Stimulant intoxication causes severe behavioural disturbance such that patients may require chemical restraint, which also significantly delays assessment.…”
Section: Effect Of Pecc On Ed Losmentioning
confidence: 99%